Hukum Membaca Al-Qur’an bagi Wanita Haid Perspektif Mazhab Hanafi dan Mazhab Maliki (Tinjauan Istihsan) - Jamilah; As'ad Badar; Alang Sidek (Journal Smart Law, 2024)
The Qur'an is a special holy book and the word of Allah SWT, the One who created humans and the entire universe. The Qur'an was revealed as a guide that saves humans from the misery of this world and the hereafter. The Qur'an is a holy book from Allah as a guide to life for worshiping Allah Almighty, that gives good news and threats, a holy book that was revealed to the Prophet Muhammad SAW, a book that is holy and guarded, a book that is straight and noble, a guide to life. Teherefore Al-Qur’an should be read, studied and understood by Muslims. In Islamic teachings, there are rules that prohibit a woman who’s menstruating from reading or touching the Qur’an. There are differences of opinion between ‘Ulama regarding the law of reading the Qur’an for menstruating women, some forbid it and some allow it. In this case, there are two Mazhabs whose differences of opinion diverge, namely Mazhab Hanafi and Mazhab Maliki. The type of research used is library research or literature study where data is collected through the process of reading and reviewing primary data sources and other relevant literature. The results of this research show that the Hanafi Mazhab prohibits menstruating women from reading the Qur’an in its entirety, Mazhab Hanafi allows menstruating women to read the Qur’an provided that they only read vocabulary and read with the intention of not reading the Qur’an, such as praying, reciting dhikr and praise Allah. As for the Mazhab Maliki, it’s absolutely permissible for menstruating women to read the Qur’an whether they have previously been junub or not, whether they’re worried about forgetting to memorize it or not and with the intention of reading it or not. Based on istihsan with mashlahah and istihsan with rejection of difficulties and difficulties.